2016
DOI: 10.1155/2016/4039837
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Chronic Zinc Administration Increases Neuroinflammation in a Hypoxia-Ischemia Model

Abstract: Acute and subacute administration of zinc exert neuroprotective effects in hypoxia-ischemia animal models; yet the effect of chronic administration of zinc still remains unknown. We addressed this issue by injecting zinc at a tolerable dose (0.5 mg/kg weight, i.p.) for 14 days before common carotid artery occlusion (CCAO) in a rat. After CCAO, the level of zinc was measured by atomic absorption spectrophotometry, nitrites were determined by Griess method, lipoperoxidation was measured by Gerard-Monnier assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 89 publications
(95 reference statements)
1
9
0
Order By: Relevance
“…Our group showed similar results in the preconditioning effect of subacute zinc administration in the CCAO rat model [ 5 ]. However, the prophylactic chronic zinc administration (0.2 mg/kg of body weight/days) exerted a partial effect because there was no memory consolidation as reported previously with a higher dose of zinc [ 19 ]. In contrast, the therapeutic administration of selenium improved the long-term memory consolidation, which is consistent with the significant decrease in neuronal cell death induced by cerebral ischemia in the temporoparietal cortex.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our group showed similar results in the preconditioning effect of subacute zinc administration in the CCAO rat model [ 5 ]. However, the prophylactic chronic zinc administration (0.2 mg/kg of body weight/days) exerted a partial effect because there was no memory consolidation as reported previously with a higher dose of zinc [ 19 ]. In contrast, the therapeutic administration of selenium improved the long-term memory consolidation, which is consistent with the significant decrease in neuronal cell death induced by cerebral ischemia in the temporoparietal cortex.…”
Section: Discussionmentioning
confidence: 96%
“…The subacute administration of zinc (2.5 mg/kg) before CCAO exerts a neuroprotective effect by increasing the expression of CCL2/CCR2, FGF2, and IGF-1 in the temporoparietal rat cortex [ 5 ]. In contrast, chronic zinc administration at a low dose (0.5 mg/kg body weight) before CCAO decreases CCL2/CCR2, CCL3/CCR1, CCL4/CCR8, and CXCL13/CXCR5 and increases CXCL12/CXCR4, but does not prevent cell death in the late phase [ 19 ]. The antioxidant effect of selenium has been used to exert neuroprotection alone [ 12 ] or in combination with other antioxidants such as melatonin [ 15 ], Ginkgo biloba [ 13 ], and alpha-tocopherol [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia may initiate an inflammatory response in the CNS and generate excess amounts of inflammatory mediators that can induce brain injury [20]. Activated microglia elicit neuroinflammation and release inflammatory cytokines such as IL-1β [21].…”
Section: Discussionmentioning
confidence: 99%
“…The De Paula et al study expressed that enormous and transient zinc accumulation during cerebral ischemia was significantly involved in brain damage through promotion of neuronal apoptotic death, so removing zinc can be a means of reducing ischemic brain injury [ 14 ]. Tomas-Sanchez et al found that despite the neuroprotective role of lower doses of zinc against cerebral ischemia, zinc accumulation leads to cytotoxicity, neuroinflammation, neuronal death, and cerebral dysfunction [ 15 ]. It also stated that the zinc serum level can be used in the detection and prevention of stroke [ 5 , 7 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of HTN in stroke patients was 65% in line with Tomas-Sanchez et al study in India. Perhaps it can be related to food culture or other similar factors in two regions that lead to high systolic and diastolic blood pressure [ 15 ]. The Galasso and Dyck study concluded that patients with antihypertension drug consumption had lower zinc serum levels in comparison to patients with no drug consumption for HTN [ 18 ].…”
Section: Discussionmentioning
confidence: 99%